(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Even though the documentation on the effects of the pandemic on educators is being done, enough spaces have not been provided to the female educators working in higher education in Nepal. In this paper, I attempt to explore the journey of navigating my emotions as an educator in Nepal working from home and hope to contribute to the broader discussions on emotions and emotional expressions. The context of this self-study is my life as an educator working in higher education between 29 March 2020 to 29 March 2021. This paper focuses on exploring the question, ‘How did the reflections of my emotions during the time of pandemic help me reconstruct my identity as an educator?’. Written as a retrospective reflection on vulnerability, courage, and empathy, self-reflective diary entries were used for data analysis. The paper shows the gendered implication on the emotional expression on me as a female faculty and how it impacted my identity as an educational leader. कोभिड-१९ महामारीले शिक्षकहरुमाथि कस्तो प्रभाव पारेको छ भन्ने कुराको अभिलेखिकरण भइरहेको भए तापनि उच्च शिक्षामा कार्यरत महिलाशिक्षकहरुका बारेमा त्यसले पर्याप्त ठाउँ दिएको छैन । यो अनुसन्धान पत्रमा म नेपालको उच्च शिक्षामा कार्यरत, घरबाट काम गर्न बाध्यमहिलाको मनोभावहरुको एउटा यात्राको रुपमा अन्वेषण गर्दछु र त्यसले महामारी नृसृत भावना र मनोभावजन्य विषयमा हुने बृहत्तर छलफलमायोगदान पुर्‍याउने आशा गर्दछु। यो स्व-अन्वेषणको परिवेश म महिला शिक्षकले नेपालको उच्च शिक्षामा काम गरेको २९ मार्च २०२० देखि २९मार्च २०२१ सम्मको समयावधि हो। यो अनुसन्धान पत्रको मूल प्रश्न महामारीमाथिका मेरा प्रतिविम्बनले कसरी मेरो पहिचानको पुनर्निर्माणमामद्दत पुर्यायो भन्ने अन्वेषण गर्दछ । कमजोरी, साहस र सहानुभूति को पूर्वब्यापी प्रतिबिम्बन भएकोले यसमा तथ्यांक विश्लेषणका लागि स्वप्रतिबिम्बित डायरीको प्रयोग गरिएको थियो। यो अनुसन्धान पत्रले महिला शिक्षकको मनोभावजन्य अभिब्यक्तिमा निहित लैङ्गिक महत्ताकासाथै कसरी त्यसले शैक्षिक नेतृका रुपमा मेरो परिचयलाई प्रभाव पार्यो भन्ने देखाउँछ।